Promoting Peace through Religious Education in Multicultural Societies: A Comparative Analysis - Maneka Tungga Darma Pertiwi; Anton Dwi Prasetiyo; Heri Setiawan Pambudi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper explores the role of religious education in fostering peace and mutual respect within multicultural societies. By analyzing case studies from various countries with diverse religious landscapes, the research identifies best practices that can be integrated into educational curricula to enhance understanding and reduce prejudice. Through a comparative approach, it examines the effectiveness of specific educational frameworks and teaching methods in bridging cultural and religious divides. The findings suggest that inclusive religious education can play a vital role in promoting social cohesion and reducing intergroup conflict.